The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Examining the Impact of Remote Work on Employees, Employers, and the State in Nigeria - Adeyinka, Mutiu Abiodun; Gbajumo-sherrif, Mariam A.; Elegbede, S. Tunde (African Journal of Economic and Business Research, 2025)
Abstract The rise of remote work, accelerated by the COVID-19 pandemic, has created significant challenges for employees, employers, and the government, complicating the management of remote teams while striving to maintain productivity and organizational cohesion. The central problem addressed in this study is the deteriorating state of employment relations marked by downsizing and layoffs, particularly in the private sector in Nigeria. This study aims to analyze the impact of remote work on these stakeholders through a systematic and thematic review based on PRISMA guidelines. Twenty four publications from 2013 to 2023 were reviewed, sourced from Google Scholar, DOAJ, Scopus, and Web of Science. The findings indicate that while organizations are beginning to adopt tools for remote work and virtual communication, these resources are primarily accessible to larger companies due to associated costs. Additionally, the study highlights the pressing need for enhanced infrastructure and structural improvements to support remote work at a societal and economic level. In conclusion, the study recommends that the government enhance infrastructural development and that organizations implement better strategies for remote work. Furthermore, individuals should pursue advancements in technology to adapt to the changing landscape. These recommendations aim to promote sustainable employment relations and economic development in Nigeria in light of the evolving digital economy.
Keywords: Employees; Employment Relations; Government; Remote Work